2022
DOI: 10.1038/s41586-022-05165-3
|View full text |Cite|
|
Sign up to set email alerts
|

Stroke genetics informs drug discovery and risk prediction across ancestries

Abstract: Previous genome-wide association studies (GWASs) of stroke — the second leading cause of death worldwide — were conducted predominantly in populations of European ancestry1,2. Here, in cross-ancestry GWAS meta-analyses of 110,182 patients who have had a stroke (five ancestries, 33% non-European) and 1,503,898 control individuals, we identify association signals for stroke and its subtypes at 89 (61 new) independent loci: 60 in primary inverse-variance-weighted analyses and 29 in secondary meta-regression and m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
90
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 272 publications
(139 citation statements)
references
References 122 publications
1
90
0
1
Order By: Relevance
“…We found several genes differentially expressed in our analysis associated with stroke outcome that have also been found in genome-wide association studies (GWAS) to be significant stroke risk loci. For example, variants rs12579302, rs10886430, rs55983834, rs2501966, rs12426667 are stroke risk loci in differentially expressed stroke outcome genes ATP2B , GRK5 , SH3PXD2A , CENPQ , HOXC4 , respectively; and intergenic variants rs2107595 and rs1487504 are stroke risk loci in differentially expressed outcome genes HDAC9 and BNC2 , respectively [ 55 ]. In addition, the genome-wide significant stroke risk locus rs7974266 was upstream of differentially expressed gene PTPN11 , rs12539561 was downstream of differentially expressed gene PIK3CG , and the 3-prime UTR variant rs42035 was downstream of differentially expressed outcome gene CDK6 [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found several genes differentially expressed in our analysis associated with stroke outcome that have also been found in genome-wide association studies (GWAS) to be significant stroke risk loci. For example, variants rs12579302, rs10886430, rs55983834, rs2501966, rs12426667 are stroke risk loci in differentially expressed stroke outcome genes ATP2B , GRK5 , SH3PXD2A , CENPQ , HOXC4 , respectively; and intergenic variants rs2107595 and rs1487504 are stroke risk loci in differentially expressed outcome genes HDAC9 and BNC2 , respectively [ 55 ]. In addition, the genome-wide significant stroke risk locus rs7974266 was upstream of differentially expressed gene PTPN11 , rs12539561 was downstream of differentially expressed gene PIK3CG , and the 3-prime UTR variant rs42035 was downstream of differentially expressed outcome gene CDK6 [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, variants rs12579302, rs10886430, rs55983834, rs2501966, rs12426667 are stroke risk loci in differentially expressed stroke outcome genes ATP2B , GRK5 , SH3PXD2A , CENPQ , HOXC4 , respectively; and intergenic variants rs2107595 and rs1487504 are stroke risk loci in differentially expressed outcome genes HDAC9 and BNC2 , respectively [ 55 ]. In addition, the genome-wide significant stroke risk locus rs7974266 was upstream of differentially expressed gene PTPN11 , rs12539561 was downstream of differentially expressed gene PIK3CG , and the 3-prime UTR variant rs42035 was downstream of differentially expressed outcome gene CDK6 [ 55 ]. Another GWAS significant protein-coding variant (rs1778155) in the PDE4DIP gene was associated with an increased risk of stroke [ 56 ] and in our data PDE4DIP was up-regulated in participants with poor vs good outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Larger GWAS could provide a more robust and generalizable GRS, but due to the rarity of ICH, GWAS efforts have been slower than for ischemic stroke. 23,40 Despite these challenges, our results demonstrate that in a score of eight different clinical risk factors for major hemorrhage, one additional point for the highest genetic ICH risk substantially improves the prediction of incident ICH. Thus, in situations with clinical equipoise, we submit that individual genetic ICH risk could be accounted for when stratifying an individual both for ICH and major hemorrhage risk.…”
Section: Discussionmentioning
confidence: 84%
“…1 The etiology of ischemic stroke, the predominant form of stroke, is multifactorial and includes both genetic and nongenetic causes. Genome-wide association studies (GWAS) have identified 89 stroke-associated loci to date 2; 3 , although these loci account for only a very small proportion of stroke heritability. A major limitation of current genome-wide approaches, which rely predominantly on genotyping arrays, is that they typically interrogate only common variation throughout the genome (eg, SNPs with minor allele frequency > 1-5%) and generally do not cover the coding regions of the genome.…”
Section: Introductionmentioning
confidence: 99%